US rebalancing strategy and the South China Sea disputes - Ralf Emmers. (2012)
The US rebalancing strategy, or “pivot” towards Asia, has added a new dimension to the South China Sea disputes. Given China’s reaction and the rising temperature in the region, is there any more room for discussion?